Combining rule-based reasoning with multi-criteria decision-making in the context of adaptive tutoring for health issues. (2015) - Kabassi, Katerina; Virvou, Maria; Tsihrintzis, George A.
This paper describes the development of an inference mechanism that is based on a hybrid combination of rule-based reasoning of double stereotypes and decision-making techniques. This inference mechanism has been applied in an intelligent medical tutor for atheromatosis. The tutor is called intelligent atheromatosis tutor (INTATU). INTATU provides adaptive tutoring on atheromatosis for various classes of users depending on their interests, background medical knowledge and computer skills. The adaptivity results from user modelling that is based on stereotypical knowledge about potential users (i.e., patients, patients' relatives, doctors, medical students, etc.). For the design of the system reasoning mechanism, and, thus, the successful incorporation of the decision-making theory, an empirical study was conducted. As soon as the full functionality of the reasoning mechanism of the system was implemented, it was evaluated in comparison to the reasoning of human experts. The results of the evaluation offer strong evidence about the effectiveness of the reasoning mechanism and the overall operation of the system.